DIAGNOSTIC SONOGRAPHY IN ANIMAL ABDOMINAL SURGERY - Dekhnych, I. S.; Zavaliy, M. F.; Rakitina, A. I. (Scientific Progress & Innovations, 2021)
The article presents materials about the history of ultrasonography in veterinary practice, analyzes the literature dealing with the liver, spleen and pancreas examination, and indicates the prospects of research methods in the future. Abdominal ultrasonography of animals was used for the first time mainly for pregnan-cy diagnostics. Today, this technique is an important diagnostic procedure in veterinary medicine, which is used to study the majority of normal and pathologically changed animal structures, providing a fast, non-invasive way to supplement the information obtained from clinical examination and radiography. Ultrasound examination is based on the principle of echolocation, the waves sent by the sensor pass through body tis-sues and are displayed and decoded by the device and converted into an image, which allows a veterinary medicine specialist to assess the condition of internal organs, tissues and cavities. With increasing using ul-trasonographic examinations by veterinary doctors in practice, it becomes clear that ultrasound diagnostics is a valuable means of detecting lesions of the abdominal cavity. Liver assessment is one of the main ad-vantages of applying animal abdominal ultrasound examination. Indications include hepatomegaly, jaundice, ascites, suspected diaphragm rupture, weight loss, and possible liver metastases. Today, the meth-ods of sonographic examination are being improved and supplemented. Further implementation in practice and in-depth study of pathologies in this area with the help of ultrasonography will allow determine objec-tively the condition of the abdominal cavity and its organs in animals and assess the severity of the disease development. The introduction of high-quality, portable diagnostic ultrasound equipment has continued this development and the demand for ultrasonography due to its diagnostic value continues to increase. The con-ducted analysis of the literature and available Internet sources allowed us to assess the current state of im-plementing sonography in veterinary practice and prospects for further development the diagnosing of the liver, spleen and pancreas condition, indicate areas of potential technique development in the future.